Plant-Mediated Changes in Soil N-Cycling Genes during Revegetation of Copper Mine Tailings - Li, Yang; Jia, Zhongjun; Sun, Qingye; Cheng, Jianhua; Yang, Yang; Zhan, Jing; Wang, Dan (Frontiers in Environmental Science, 2017)
Nitrogen limitation represents a major bottleneck during the revegetation of mine tailings. However, controls over key nitrogen-cycling genes in rhizospheric soils under differential vegetation management remain poorly understood. The abundance and transcriptional activity of nitrogen-cycling genes and the enzymatic activity of nitrogen transformation are mediated differentially during revegetation of mine tailings by Imperata cylindrica and Chrysopogon zizanioides plants. Results showed that the highest total organic carbon (TOC), total nitrogen (TN) and NH4+-N contents were found in the rhizosphere of I. cylindrica. The nifH gene abundances differed between I. cylindrica and C. zizanioides, and were higher in I. cylindrica which demonstrated by 3.39-fold higher mRNA transcript abundance of the nifH gene and a 2.15-fold higher nitrogen fixation rate in the rhizosphere. In addition, C. zizanioides exhibited a 4.94-fold higher transcript abundance of the archaeal amoA gene and the highest nitrification rate (1.706±0.293 µg N-NO2- g-1 h-1) in the rhizosphere. In conclusion, I. cylindrica and C. zizanioides stimulated the abundances and activities of nifH gene and archaeal amoA gene, respectively. In addition, I. cylindrica appears to be capable of enhancing nitrogen fixation and exhibited accelerated nitrogen accumulation, which may be particularly useful for the rehabilitation of mine tailings.